The crystal structure of 5-benzoyl-1-[(E)-(4-fluorobenzylidene)amino]-4-phenylpyrimidin-2(1H)-one, C24H16FN3O2 - Atioğlu Zeliha; Karataş Halis; Kökbudak Zülbiye (Zeitschrift für Kristallographie - New Crystal Structures)
C24H16FN3O2, monoclinic, P21 (no. 4), a = 6.0024(5) Å, b = 19.474(2) Å, c = 8.3531(8) Å, β = 91.750(9)°, V = 975.95(16) Å3, Z = 2, R gt(F) = 0.0409, wR ref(F 2) = 0.0832, T = 294(2) K.